Herbal Medicine as Neuroprotective Potential Agent in Human and Animal Models: A Historical Overview - Arash Abdolmaleki; Muhammad Akram; Muhammad Muddasar Saeed; Asadollah Asadi; Mahan Kajkolah (Research Center for Rational Use of Drugs (RCRUD), 2020)
Neurodegenerative disorders could be a most important health issue within the 21st century. In the recent past; there has been a growing interest in medicinal plants. Chemical fruits and vegetables are said to decrease the possibility of many chief ailments, together with cardiovascular and cancer disorders as well as neurodegenerative ailments. Hence, who eat more fruits and vegetables may be less threat of developing certain diseases caused by neurological dysfunction. The present review provides an overview of the most important plants used for neurological disorders and explores their neurological protection for the development of new pharmacological potential drugs. The data sources included Pubmed and PMC Pubmed Central articles on the topic. Therefore, we present a systematic approach for Herbal medicine as neuroprotective agent. From ancient time the herbal medicines are used to cure neurological symptoms. While the exact pharmacology of these herbs has not yet been set on, some of them have anti-inflammatory or antioxidant properties on different peripheral systems. The significant variety of medicinal plants makes it an essential source of healthy compounds compared to current therapeutic agents. In this review, the importance of phytochemicals for the function of neurological protection and other related disorders, in particular, the process mechanism and therapeutic prospective will be emphasize.